Relative bioefficacy of RRR-α-tocopherol versus all-rac-α-tocopherol in in vitro models (International Journal of Health, Animal Science and Food Safety, 2015)
The aim of this study was to evaluate the in vitro relative bioefficacy of RRR-α-tocopherol (RRR- α-T) versus all-rac-α-tocopherol (all-rac-α-T) in counteracting the cytotoxic effect induced by H2O2 in Bovine Mammary Epithelium – University of Vermont (BME-UV1) and Madin-Darby Canine Kidney (MDCK) cells. The range of RRR- α-T and all-rac- α-T concentrations selected for the oxidative challenge experiments was 100µM - 1nM. To study the bioefficacy of RRR- α-T and all-rac- α-T, MTT and LDH tests were performed. Cells were pre-incubated for 3 h with  selected a-tocopherol concentrations and then exposed to increasing H2O2 concentrations ranging from 125 to 750µM for the following 24h. Concerning the cell viability, the pre-treatments with 100µM of RRR- α-T and 100µM all-rac-α-T were able to significantly (P
Keywords: RRR-α-tocopherol; all-rac-α-tocopherol; in vitro models